Contemporary Expressions of Sufism: The Naqshbandi Haqqani Order in the Urban Context of Padang - Putra, Johan Septian; Karali, Nurcan (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Urban society is significantly shaped by modernization, with modernity and globalization influencing all facets of culture, religion, politics, and law. These shifts pose challenges for traditional Sufi orders, particularly in adapting to technological advances, social changes, and evolving economic-political landscapes. Sufi order Naqshabandi Haqqani exemplifies a sufi order that effectively responds to modernity through inclusive preaching methods, digital engagement, and social adaptability, while preserving its spiritual essence. This qualitative field research explores how the order adapts to digital technology, approaches social transformation, and maintains relevance in a globalized world. Findings reveal three key aspects: First, the order has expanded significantly in urban areas, attracting followers from various social backgrounds, including elites and bureaucrats. Second, it employs adaptive strategies by embracing innovation and using digital platforms to reach wider and younger audiences. Third, the order adopts a flexible and “easy-going” approach to some Sufi practices, minimizing esoteric and intense philosophical elements that might deter new adherents. This approach reflects a phenomenon of continuity and change, wherein core spiritual teachings are preserved while their presentation and practice evolve to meet contemporary societal needs. As a result, the order remains accessible, relevant, and spiritually meaningful within a modern, digitalized context.